Endovascular thrombectomy in acute ischemic stroke patients with prestroke disability (mRS ≥2): A systematic review and meta-analysis - Yang, Jin-Cai; Bao, Qiang-Ji; Guo, Yu; Chen, Shu-Jun; Zhang, Jin-Tao; Zhang, Qiang; Zhou, Ping; Yang, Ming-Fei (Frontiers in Neurology, 2022)
Objective: The effect of endovascular thrombectomy (EVT) in acute ischemic stroke patients with prestroke disability (modified Rankin Scale score, mRS) ≥2) has not been well studied. This study aimed to assess the safety and benefit of EVT in patients with prestroke disability. Methods: According to PRISMA guidelines, literature searching was performed using PubMed, Embase, and Cochrane databases, for series of acute ischemic stroke patients with prestroke mRS ≥2 treated by EVT. Random-effects meta-analysis was used to pool the rate of return to prestroke mRS and mortality at 3-month follow-up. Results: Totally 13 observational studies, with 2625 patients, were analyzed. The rates of return to prestroke mRS in patients with prestroke mRS of 2 to 4 were was 20% (120/588), 27% (218/827) and 31% (34/108), respectively. Patients with prestroke disability treated by EVT had higher likelihood of return to prestroke mRS (relative risk, RR, 1.86; 95% confidence interval, CI, 1.28-2.70) and lower likelihood of mortality (RR 0.75; 95%CI 0.58-0.97) compared with patients with standard medical treatment. Successful recanalization (Thrombolysis in Cerebral Infarction grade 2b-3) after EVT gave higher likelihood of return to prestroke mRS (RR 2.04; 95% CI 1.17-3.55) and lower mortality (RR 0.72; 95% CI 0.62-0.84) compared with unsuccessful reperfusion. Conclusions: Acute ischemic stroke patients with prestroke disability may benefit from EVT. Withholding EVT on the sole ground of prestroke disabilities may not be justified.